Perception of students Repertory Ecological Problems of the School of General Studies curriculum course elements as well as promoting environmental education - Jiménez-Morales, Ana Patricia (2015)
This paper evaluates the perception of the students of the Repertoire of Ecological Problems of the 2nd half of 2013, through a survey to 200 students. The perception of informants about the evaluated aspects of the course is highly positive. In all the items evaluated students qualified the course of very good to excellent, the percentages ranging between 65% and 96%. The results of the survey confirm us that the course is in according with the three pillars of the University: teaching, research and social expansion. Both the research and social action (environmental action) focusing on the national reality. The course carries out an environmental education among students, promoting the development of a strong environmental awareness that will support their professional development. Students are satisfied with the course and with activities such as environmental action and the study field trips, which are considered by them very important.